The Effect of Rewards and Career Development on Employee Performance at PT. Telkom Bengkulu Branch - Dicky Stiawan; Eti Arini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this study was to find out whether rewards and career development simultaneously have a significant effect on employee performance at PT. Telkom Bengkulu Branch. This research is a type of quantitative research. Data collection techniques are documentation, observation and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of research on the effect of reward, career development and service quality on the performance of consumer employees at PT. Telkom Bengkulu, it can be concluded that Reward (X1) has a positive and significant effect on the performance of employees (Y) of PT. Telkom Bengkulu means increasing the rewards given by the company to employees, thus increasing employee performance. Career development (X2) has a positive and significant effect on employee performance (Y) PT. Telkom Bengkulu means that the career development provided by the company to employees increases, the employee performance increases. Rewards and career development jointly affect the performance of employees of PT. Telkom Bengkulu.